Muslim Utopia: Gerakan dan Pemikiran Politik Hizbut Tahrir Indonesia (HTI) Pasca-Reformasi - M. Zaki Mubarak (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2007)
Hizbut Tahrir (HT), an organization founded by Taqiuddin al-Nabhani in 1953, is a political party with an Islamic ideology. Politics is the avenue through which HT pursues its mission, and its ideology is Islam. HT's struggle is aimed at making Islam its primary concern, guiding towards the reestablishment of the caliphate system, and upholding the laws descended by Allah in the reality of life. Through various political activities, HT intends to revive the Muslim community from decline, free Muslims from ideas, legal systems, and laws that are considered disbelieving, and seeks to break free from the domination of Western infidel states. HT aims to rebuild the Islamic Caliphate on Earth. What about Hizbut Tahrir Indonesia (HTI)? This writing presents the profile of HTI, from its origins, thoughts, to its political movements, especially in the post-reform era in Indonesia.